KAJIAN TENTANG SISTEM PENGENALAN AIR MINERAL KEMASAN GELAS BERDASARKAN LOGO DENGAN METODE HISTOGRAM OF ORIENTED GRADIENTS - Yudhistira Anggara D; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Application System for the Introduction of Mineral Water Glass Packaging Based on the Logo with the Histogram of Oriented Gradients method is an application used to carry out brand recognition or the logo of glass packaging mineral water. This game is designed on Windows operating systems and uses Python software, and OpenCV. The methods used in this design are the Histogram of Oriented Gradients as a method for feature extraction, the Euclidean Distance method as a method for measuring similarity distances, and k-Nearest Neighbor as a method of recognizing logos or brands.